Pemberdayaan Kader PKK Melalui Pendidikan Ekonomi untuk Meningkatkan Kewirausahaan dan Pengelolaan Keuangan di Wilayah Perdesaan - Luh Indrayani; Ni Wayan Ayu Santi; I Nyoman Sujana (Jurnal Pengabdian UNDIKMA, 2026)
This community service program aims to enhance women’s knowledge and skills through the application of economic education to strengthen entrepreneurship and financial management among members of the Family Welfare Empowerment (PKK) cadres in Banjar Dinas Santal, Mayong Village, Bali. The program was implemented using a participatory approach that included education, training, and mentoring activities. Program evaluation was conducted through comparisons of pre-test and post-test results, analysis of business financial records, and assessment of improvements in digital marketing comprehension. Data were analyzed using both quantitative and qualitative techniques. The results indicate a significant improvement in the capacity of PKK cadres in financial management, financial record-keeping, and digital marketing. The average score for basic financial management understanding increased from 70 to 90, reflecting improved mastery of business financial planning and recording concepts. Approximately 90% of participants have consistently implemented structured financial record-keeping systems. In addition, 86.7% of PKK cadres demonstrated proficiency in digital marketing techniques, particularly in utilizing social media as a promotional tool. These findings confirm that the implemented community service program was effective in enhancing partners’ competencies, business independence, and professionalism.